Epitaxial growth of III-nitride nanostructures and applications for visible emitters and energy generation - Pantha, Bed Nidhi (Kansas State University, 2009)
III-nitride nanostructures and devices were synthesized by metal organic chemical vapor deposition (MOCVD) for their applications in various photonic, optoelectronic, and energy devices such as deep ultraviolet (DUV) photodetectors, solar cells, visible emitters, thermometric (TE) power generators, etc. Structural and optical properties in thicker AlN epilayers were found to be better than those in thinner AlN epilayers. Full-width at half maxima (FWHM) of x-ray diffraction (XRD) rocking curves as small as 63 and 437 arcsec were measured at (002) and (102) reflections, respectively in a thick AlN epilayer (4 m). The dark current of the fabricated AlN detectors decreases drastically as AlN epilayer thickness increases. DUV photoluminescence (PL) spectroscopy and x-ray diffraction (XRD) measurements were employed to study the effect of biaxial stress in AlN epilayers grown on different substrates. Stress-induced band gap shift of 45 meV/GPa was obtained in AlN epilayers. The potential of InGaN alloys as TE materials for thermopower generation has been investigated. It was found that as In content increases, thermal conductivity decreases and power factor increases, which leads to an increase in the TE figure of merit (ZT). The value of ZT was found to be 0.08 at 300 K and reached 0.23 at 450 K for In0.36Ga0.64N alloy, which is comparable to that of SiGe based alloys. Single phase InxGa1−xN alloys inside the theoretically predicted miscibility gap region (x = 0.4 to 0.7) were successfully synthesized. A single peak of XRD -2 scans of the (002) plane in InGaN alloys confirms that there is no phase separation. Electrical properties and surface morphologies were found to be reasonably good. It was found that growth rate should be high enough (>400 nm/hr) to achieve high quality and single phase InxGa1−xN alloys in this miscibility gap region. Mg-doped InxGa1-xN alloys were synthesized and characterized by Hall-effect and PL measurements for their application as visible emitters. P-type conductivity was measured up to x = 0.35 with accepter activation energy as low as 43 meV, which is about 4 times lower than that of Mg-doped p-type GaN. Resistivity as low as 0.4 -cm with a free hole concentration as high as 5x1018 cm-3 was measured in Mg-doped In0.22Ga0.78N. PL intensity decreased ~3 orders in magnitude when x increased from 0 to 0.22 in Mg-doped InxGa1-xN alloys.
Keywords: III-nitrides; MOCVD; Thermoelectric; InGaN; Dislocation; XRD; Physics, Condensed Matter (0611)